Olefin-based polymer, film produced therefrom, and method for producing same

The olefin polymer, produced with a hybrid catalyst system, addresses poor processability and mechanical strength issues by achieving high drop impact strength and improved processability, suitable for films requiring mechanical resilience.

JP7603162B2Active Publication Date: 2024-12-19HANWHA SOLUTIONS CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023534615
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-08
Filing Date
2021-12-02
Publication Date
2024-12-19
Estimated Expiration
2041-12-02

AI Technical Summary

Technical Problem

Existing olefin polymers produced using metallocene catalysts suffer from poor processability due to narrow molecular weight distribution, limiting their application in films requiring high mechanical strength, particularly drop impact strength.

Method used

An olefin polymer with a density of 0.9 to 0.95 g/cm³, melting index of 0.1 to 5.0 g/10 min, melt flow ratio of 20 or more, and shear thinning index defined by a specific formula, produced using a hybrid catalyst system, exhibits an extrusion load of 270 Nm or less, resulting in films with a drop impact strength of 700 g or more.

Benefits of technology

The olefin polymer achieves excellent processability and mechanical strength, particularly in films with enhanced drop impact strength, suitable for applications such as stretch films and agricultural wraps.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603162000022
    Figure 0007603162000022
  • Figure 0007603162000023
    Figure 0007603162000023
  • Figure 0007603162000001
    Figure 0007603162000001
Patent Text Reader

Abstract

The present invention relates to an olefin polymer, a film produced therefrom, and a method for producing the same. The olefin polymer according to the embodiment of the present invention has excellent processability, and a film produced therefrom, in particular a linear low-density polyethylene film, has excellent mechanical strength, in particular drop impact strength.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an olefin-based polymer, a film produced therefrom, and a method for producing the same, and more particularly to an olefin-based polymer film produced therefrom and having excellent mechanical strength, in particular drop impact strength, and a method for producing the same. [Background technology]

[0002] Metallocene catalysts, which are one of the catalysts used to polymerize olefins, are compounds in which ligands such as cyclopentadienyl, indenyl, or cycloheptadienyl are coordinated to a transition metal or a transition metal halide, and have a sandwich structure as their basic structure.

[0003] Ziegler-Natta catalysts, another catalyst used to polymerize olefins, have metal components that act as active sites dispersed on an inert solid surface, and the properties of the active sites are not uniform. On the other hand, metallocene catalysts are a single compound with a fixed structure, and are known as single-site catalysts, in which all active sites have the same polymerization properties. Polymers polymerized with such metallocene catalysts have narrow molecular weight distributions, uniform comonomer distributions, and higher copolymerization activity than Ziegler-Natta catalysts.

[0004] Meanwhile, linear low-density polyethylene (LLDPE) is produced by copolymerizing ethylene and α-olefins at low pressure using a polymerization catalyst, and has a narrow molecular weight distribution, short chain branches (SCB) of a certain length, and generally no long chain branches (LCB). Films produced from linear low-density polyethylene have high breaking strength and elongation, excellent tear strength, impact strength, etc. in addition to the general properties of polyethylene, so they are widely used in stretch films and overlap films where it is difficult to use conventional low-density polyethylene or high-density polyethylene.

[0005] However, linear low density polyethylene produced by a metallocene catalyst tends to have poor processability due to a narrow molecular weight distribution. Therefore, there is a demand for an olefin polymer which can be used to produce a film having excellent processability and mechanical strength, particularly excellent drop impact strength. Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide an olefin polymer from which an olefin polymer film having excellent processability and mechanical strength, particularly excellent drop impact strength, can be produced.

[0007] Another object of the present invention is to provide an olefin polymer film which is produced from the above olefin polymer and which has excellent mechanical strength, particularly excellent drop impact strength. It is still another object of the present invention to provide a method for producing the olefin polymer and the olefin polymer film. [Means for solving the problem]

[0008] According to one embodiment of the present invention, (1) the density is 0.9 to 0.95 g / cm 3 (2) Melt index (I 2.16 (3) the melt index (I 21.6 ) and the melt index (I 2.16 (3) an olefin-based polymer having a melt flow ratio (MFR) of 20 or more, (4) a shear thinning index defined by the following mathematical formula 1 of 8 to 15, and (5) an extrusion torque of 270 Nm or less at an extrusion rate of 5.8 to 5.9 kg / hr, and a film produced therefrom has a drop impact strength (B type) of 700 g or more, preferably 700 to 2,000 g, based on a thickness of 50 μm.

[0009] [Formula 1] Shear thinning index = η0 / η 500

[0010] Where η and η 500 are the complex viscosities at frequencies of 0.1 rad / s and 500 rad / s, respectively.

[0011] In a specific example of the present invention, the olefin polymer has: (1) a density of 0.915 to 0.945 g / cm 3 (2) Melt index (I 2.16 (3) the melt index (I 21.6 ) and the melt index (I 2.16(4) a melt flow ratio (MFR) of 20 or more, (5) a shear thinning index defined by Equation 1 of 9 to 15, and (6) an extrusion torque of 260 Nm or less at an extrusion rate of 5.8 to 5.9 kg / hr. A film produced therefrom may have a drop impact strength (B type) of 700 g or more based on a thickness of 50 μm.

[0012] In a preferred embodiment of the present invention, the olefin polymer has: (1) a density of the olefin polymer of 0.915 to 0.942 g / cm 3 (2) the melt index measured at 190°C under a load of 2.16 kg is 0.5 to 3.5 g / 10 min; (3) the MFR is 20 to 50; (4) the shear thinning index defined by Equation 1 is 9 to 12; and (5) the extrusion load at an extrusion rate of 5.8 to 5.9 kg / hr may be 200 to 255 Nm.

[0013] In a specific example of the present invention, the olefin polymer may be prepared by polymerizing an olefin monomer in the presence of a hybrid catalyst including at least one first transition metal compound represented by the following chemical formula 1 and at least one second transition metal compound selected from the group consisting of a compound represented by the following chemical formula 2 and a compound represented by the following chemical formula 3:

[0014] [ka]

[0015] [ka]

[0016] [ka]

[0017] In the Chemical Formulas 1 to 3, M1 and M2 are different from each other and each independently represent titanium (Ti), zirconium (Zr), or hafnium (Hf); X is independently halogen, C 1-20 Alkyl, C 2-20 Alkenyl, C 2-20 Alkynyl, C 6-20 Aryl, C 1-20 Alkyl C 6-20 Aryl, C 6-20 Aryl C 1-20 Alkyl, or C 1-20 is an alkyl amide, R1~R 10 each independently represents hydrogen, a substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 2-20 Alkenyl, substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 1-20 Alkyl C 6-20 Aryl, substituted or unsubstituted C 6-20 Aryl C 1-20 Alkyl, substituted or unsubstituted C 1-20 Heteroalkyl, substituted or unsubstituted C 3-20 Heteroaryl, substituted or unsubstituted C 1-20 Alkylamide, substituted or unsubstituted C 6-20 Arylamide, substituted or unsubstituted C 1-20 Alkylidene, or substituted or unsubstituted C 1-20 Cyril, R1 to R 10 each independently represents a substituted or unsubstituted, saturated or unsaturated C 4-20 A ring may be formed.

[0018] In an embodiment of the present invention, M1 and M2 are different from each other and each is zirconium or hafnium, and X is each halogen or C. 1-20 alkyl, R to R 10 are hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 1-20Alkenyl, or substituted or unsubstituted C 6-20 It may be aryl. In a preferred embodiment of the invention, M1 is hafnium, M2 is zirconium, and X may be chlorine or methyl.

[0019] In a preferred embodiment of the present invention, the first transition metal compound may be at least one of the transition metal compounds represented by the following chemical formulas 1-1 and 1-2, and the second transition metal compound may be at least one of the transition metal compounds represented by the following chemical formulas 2-1, 2-2, and 3-1.

[0020] [ka]

[0021] [ka] In the above formula, Me is a methyl group.

[0022] In an embodiment of the present invention, the molar ratio of the secondary transition metal compound to the first transition metal compound ranges from 100:1 to 1:100.

[0023] In a specific example of the present invention, the catalyst may include at least one promoter selected from the group consisting of a compound represented by the following formula 4, a compound represented by the following formula 5, and a compound represented by the following formula 6:

[0024] [ka]

[0025] [ka]

[0026] [Chemical formula 6] [LH] + [Z(A)4] -or [L] + [Z(A)4] -

[0027] In the above Chemical Formula 4, n is an integer of 2 or more, and R a is a halogen atom, C 1-20 Hydrocarbon or halogen-substituted C 1-20 is a hydrocarbon group, In the above formula 5, D is aluminum (Al) or boron (B), and R b , R c , and R d are each independently a halogen atom, C 1-20 Hydrocarbon radicals, halogen-substituted C 1-20 Hydrocarbon group, or C 1-20 is an alkoxy group, In the above formula 6, L is a neutral or cationic Lewis base, [LH] + and [L] + is a Bronsted acid, Z is a Group 13 element, and each A is independently a substituted or unsubstituted C 6-20 an aryl group or a substituted or unsubstituted C 1-20 It is an alkyl group.

[0028] In an embodiment of the present invention, the catalyst may further comprise a support supporting the transition metal compound, the cocatalyst compound, or both. In a preferred embodiment of the present invention, the support may comprise at least one selected from the group consisting of silica, alumina, and magnesia.

[0029] Here, the total amount of the hybrid transition metal compounds supported on the support is 0.001 to 1 mmole based on 1 g of the support, and the total amount of the promoter compounds supported on the support is 2 to 15 mmole based on 1 g of the support.

[0030] In a specific example of the present invention, the olefin polymer is a copolymer of an olefin monomer and an olefin comonomer. Specifically, the olefin monomer may be ethylene, and the olefin comonomer may be at least one selected from the group consisting of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, and 1-hexadecene. Preferably, the olefin polymer is a linear low-density polyethylene in which the olefin monomer is ethylene and the olefin comonomer is 1-hexene.

[0031] According to one embodiment of the present invention, the present invention includes a step of polymerizing an olefin-based monomer in the presence of a hybrid catalyst containing at least one first transition metal compound represented by the above Chemical Formula 1 and at least one second transition metal compound selected from the group consisting of the compound represented by the above Chemical Formula 2 and the compound represented by the above Chemical Formula 3 to obtain an olefin-based polymer, and (1) the density of the olefin-based polymer is 0.9 to 0.95 g / cm. 3 , preferably 0.91 to 0.945 g / cm 3 (2) Melt index (I 2.16 (3) a melt index (I) measured at 190° C. under a load of 21.6 kg; 21.6 ) and the melt index (I 2.16 (4) a melt flow ratio (MFR) of 20 or more, preferably 22 or more, (5) a shear thinning index defined by the above mathematical formula 1 of 8 to 15, preferably 9 to 15, and (6) an extrusion torque of 270 Nm or less, preferably 260 Nm or less at an extrusion rate of 5.8 to 5.9 kg / hr, and a film produced therefrom has a drop impact strength (B type) of 700 g or more, preferably 700 to 2,000 g, based on a thickness of 50 μm.

[0032] In an embodiment of the present invention, the polymerization of the olefinic monomer may be carried out by gas phase polymerization, specifically, the polymerization of the olefinic monomer may be carried out in a gas phase fluidized bed reactor. Effect of the Invention

[0033] The olefin polymer according to the embodiment of the present invention has excellent processability, and a film produced therefrom, in particular a linear low density polyethylene film, has excellent mechanical strength, particularly drop impact strength. [Brief description of the drawings]

[0034] [Figure 1] 1 is a graph showing the complex viscosity as a function of frequency for the olefin polymers of Examples 1 and 2 and Comparative Example 1. [Diagram 2] 1 is a graph showing the extrusion torque as a function of the extrusion rate of olefin polymers of Examples 1 and 2 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] The present invention will now be described in more detail. Olefin Polymers According to one embodiment of the present invention, (1) the density is 0.9 to 0.95 g / cm 3 (2) Melt index (I 2.16 (3) the melt index (I 21.6 ) and the melt index (I 2.16(3) an olefin-based polymer having a melt flow ratio (MFR) of 20 or more, (4) a shear thinning index defined by the following mathematical formula 1 of 8 to 15, and (5) an extrusion torque of 270 Nm or less at an extrusion rate of 5.8 to 5.9 kg / hr, and a film produced therefrom has a drop impact strength (B type) of 700 g or more, preferably 700 to 2,000 g, based on a thickness of 50 μm.

[0036] In a specific example of the present invention, the olefin polymer has: (1) a density of 0.915 to 0.945 g / cm 3 (2) Melt index (I 2.16 (3) the melt index (I 21.6 ) and the melt index (I 2.16 (4) a melt flow ratio (MFR) of 20 or more, (5) a shear thinning index defined by Equation 1 of 9 to 15, and (6) an extrusion torque of 260 Nm or less at an extrusion rate of 5.8 to 5.9 kg / hr. A film produced therefrom may have a drop impact strength (B type) of 700 g or more based on a thickness of 50 μm.

[0037] In a preferred embodiment of the present invention, the olefin polymer has: (1) a density of the olefin polymer of 0.915 to 0.942 g / cm 3 (2) the melt index measured at 190°C under a load of 2.16 kg is 0.5 to 3.5 g / 10 min; (3) the MFR is 20 to 50; (4) the shear thinning index defined by Equation 1 is 9 to 12; and (5) the extrusion load at an extrusion rate of 5.8 to 5.9 kg / hr may be 200 to 255 Nm.

[0038] In a specific example of the present invention, the olefin polymer has a density of 0.9 to 0.95 g / cm3 Preferably, the density of the olefin polymer is 0.91 to 0.945 g / cm. 3 , 0.915~0.945g / cm 3 , 0.91~0.93g / cm 3 , 0.915~0.942g / cm 3 , or 0.915~0.925g / cm 3 may be also possible.

[0039] In an embodiment of the present invention, the olefin polymer has a melt index (I 2.16 The melt index of the olefin polymer measured at 190° C. under a load of 2.16 kg may be preferably 0.3 to 4.0 g / 10 min, 0.5 to 3.5 g / 10 min, or 0.5 to 3.0 g / 10 min.

[0040] In an embodiment of the present invention, the olefin polymer has a melt index (I 21.6 ) and the melt index (I 2.16 ) is not less than 20. Preferably, the MFR of the olefin polymer is not less than 22 or may be 20-50.

[0041] In a specific example of the present invention, the olefin polymer has a shear thinning index defined by the following mathematical formula 1 of 8 to 15. Preferably, the olefin polymer may have a shear thinning index of 9 to 15 or 9 to 12.

[0042] [Formula 1] Shear thinning index = η0 / η 500

[0043] Where η and η 500 are the complex viscosities at frequencies of 0.1 rad / s and 500 rad / s, respectively.

[0044] Polymers, in the molten state, have a property intermediate between a completely elastic material and a viscous liquid, which is called viscoelasticity. In other words, when polymers are subjected to shear stress in the molten state, their deformation is not proportional to the shear stress, and their viscosity changes according to the shear stress. This property is understood to be due to the fact that polymers have large molecular sizes and complex intermolecular structures.

[0045] In particular, when manufacturing molded products using polymers, the shear thinning phenomenon is an important consideration. Shear thinning refers to a phenomenon in which the viscosity of a polymer decreases as the shear rate increases, and this shear thinning characteristic has a significant impact on the molding method of the polymer.

[0046] The larger the shear thinning index, the higher the complex viscosity at low frequencies and the lower the complex viscosity at high frequencies, and therefore the more excellent the physical properties and processability of the polymer can be.

[0047] In a specific example of the present invention, the olefin polymer has an extrusion torque of 270 Nm or less at an extrusion rate of 5.8 to 5.9 kg / hr. Preferably, the extrusion torque of the olefin polymer at an extrusion rate of 5.8 to 5.9 kg / hr is 260 Nm or less or 200 to 255 Nm.

[0048] In a specific example of the present invention, a film made from an olefin polymer has a drop impact strength of 700 g or more based on a thickness of 50 μm. Preferably, a film made from an olefin polymer may have a drop impact strength of 700 to 2,000 g based on a thickness of 50 μm.

[0049] The olefin polymer according to the embodiment of the present invention has a relatively broad molecular weight distribution and a relatively large amount of short chain branches in the high molecular weight component, and therefore, it is understood that the olefin polymer film produced therefrom has excellent mechanical strength, particularly drop impact strength.

[0050] In embodiments of the present invention, the olefin polymer films may be effectively used as stretch films, overwrap films, ramie, silage wrap, agricultural films, and the like.

[0051] In the specific example of the present invention, the method of forming a film from the olefin polymer according to the embodiment of the present invention is not particularly limited, and a forming method known in the technical field to which the present invention belongs may be used. For example, the above-mentioned olefin polymer may be processed by a conventional method such as inflation film (blown film) forming, extrusion forming, casting forming, etc. Among them, inflation film forming is the most preferable.

[0052] In a specific example of the present invention, the olefin polymer may be produced by polymerizing an olefin monomer in the presence of a hybrid catalyst containing at least one first transition metal compound represented by the following chemical formula 1 and at least one second transition metal compound selected from the group consisting of a compound represented by the following chemical formula 2 and a compound represented by the following chemical formula 3:

[0053] [ka]

[0054] [ka]

[0055] [ka]

[0056] In the above Chemical Formula 1 to Chemical Formula 3, M1 and M2 are different from each other and are each independently titanium (Ti), zirconium (Zr), or hafnium (Hf). Specifically, M1 and M2 are different from each other and may be zirconium or hafnium. Preferably, M1 may be hafnium, and M2 may be zirconium.

[0057] X is independently halogen, C 1-20 Alkyl, C 2-20 Alkenyl, C 2-20 Alkynyl, C 6-20 Aryl, C 1-20 Alkyl C 6-20 Aryl, C 6-20 Aryl C 1-20 Alkyl, C 1-20 Alkylamide, or C 6-20 Specifically, X is a halogen or C 1-20 It may be alkyl. Preferably, X is chlorine or methyl.

[0058] R1~R 10 each independently represents hydrogen, a substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 2-20 Alkenyl, substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 1-20 Alkyl C 6-20 Aryl, substituted or unsubstituted C 6-20 Aryl C 1-20 Alkyl, substituted or unsubstituted C 1-20 Heteroalkyl, substituted or unsubstituted C 3-20 Heteroaryl, substituted or unsubstituted C 1-20 Alkylamide, substituted or unsubstituted C 6-20 Arylamide, substituted or unsubstituted C 1-20 Alkylidene, or substituted or unsubstituted C 1-20 silyl, where R to R 10 each independently represents a substituted or unsubstituted, saturated or unsaturated C4-20 Specifically, R to R 10 are hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 1-20 Alkenyl, or substituted or unsubstituted C 6-20 It may be aryl.

[0059] In an embodiment of the present invention, M1 and M2 are different from each other and each is zirconium or hafnium, and X is each halogen or C. 1-20 alkyl, R to R 10 are hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 1-20 Alkenyl, or substituted or unsubstituted C 6-20 It may be aryl. In a preferred embodiment of the invention, M1 is hafnium, M2 is zirconium, and X may be chlorine or methyl.

[0060] In a preferred embodiment of the present invention, the first transition metal compound may be at least one of the transition metal compounds represented by the following chemical formulas 1-1 and 1-2, and the second transition metal compound may be at least one of the transition metal compounds represented by the following chemical formulas 2-1, 2-2, and 3-1.

[0061] [ka]

[0062] [ka] In the above formula, Me is a methyl group.

[0063] In a specific example of the present invention, the molar ratio of the second transition metal compound to the first transition metal compound is in the range of 100:1 to 1:100. Preferably, the molar ratio of the second transition metal compound to the first transition metal compound is in the range of 50:1 to 1:50. Preferably, the molar ratio of the second transition metal compound to the first transition metal compound is in the range of 10:1 to 1:10.

[0064] In a specific example of the present invention, the catalyst may include at least one promoter compound selected from the group consisting of a compound represented by the following formula 4, a compound represented by the following formula 5, and a compound represented by the following formula 6:

[0065] [ka]

[0066] In the above Chemical Formula 4, n is an integer of 2 or more, and R a is a halogen atom, C 1-20 Hydrocarbon or halogen-substituted C 1-20 Specifically, R a may be methyl, ethyl, n-butyl, or isobutyl.

[0067] [ka]

[0068] In the above formula 5, D is aluminum (Al) or boron (B), and R b , R c , and R d are each independently a halogen atom, C 1-20 Hydrocarbon radicals, halogen-substituted C 1-20 Hydrocarbon group, or C 1-20 Specifically, when D is aluminum (Al), R b , R c , and R d may each independently be methyl or isobutyl, and when D is boron (B), Rb , R c , and R d may each be pentafluorophenyl.

[0069] [Chemical formula 6] [LH] + [Z(A)4] - or [L] + [Z(A)4] -

[0070] In the above formula 6, L is a neutral or cationic Lewis base, [LH] + and [L] + is a Bronsted acid, Z is a Group 13 element, and each A is independently a substituted or unsubstituted C 6-20 an aryl group or a substituted or unsubstituted C 1-20 It is an alkyl group. Specifically, [LH] + may be a dimethylanilinium cation, [Z(A)4] - is [B(C6F5)4] - [L] + is [(C6H5)3C] + may be also possible.

[0071] Specifically, examples of the compound represented by Chemical Formula 4 include methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, butylaluminoxane, etc., and methylaluminoxane is preferred, but is not limited thereto.

[0072] Examples of the compound represented by Chemical Formula 5 include trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, dimethylchloroaluminum, triisopropylaluminum, tri-s-butylaluminum, tricyclopentylaluminum, tripentylaluminum, triisopentylaluminum, trihexylaluminum, trioctylaluminum, ethyldimethylaluminum, methyldiethylaluminum, triphenylaluminum, tri-p-tolylaluminum, dimethylaluminum methoxide, dimethylaluminum ethoxide, trimethylboron, triethylboron, triisobutylboron, tripropylboron, and tributylboron, among which trimethylaluminum, triethylaluminum, and triisobutylaluminum are preferred, but are not limited thereto.

[0073] Examples of the compound represented by Chemical Formula 6 include triethylammonium tetraphenylboron, tributylammonium tetraphenylboron, trimethylammonium tetraphenylboron, tripropylammonium tetraphenylboron, trimethylammonium tetra(p-tolyl)boron, trimethylammonium tetra(o,p-dimethylphenyl)boron, tributylammonium tetra(p-trifluoromethylphenyl)boron, trimethylammonium tetra(p-trifluoromethylphenyl)boron, tributylammonium tetrapentafluorophenylboron, N,N-diethylanilinium tetraphenylboron, N,N-diethylanilinium tetrapentafluorophenylboron, diethylammonium tetrapentafluorophenylboron, triphenylphosphonium tetraphenylboron, trimethylphosphonium tetraphenylboron, triethylammonium tetraphenylaluminum, and tributylammonium tetraphenylaluminum. ammonium, trimethylammonium tetraphenylaluminum, tripropylammonium tetraphenylaluminum, trimethylammonium tetra(p-tolyl)aluminum, tripropylammonium tetra(p-tolyl)aluminum, triethylammonium tetra(o,p-dimethylphenyl)aluminum, tributylammonium tetra(p-trifluoromethylphenyl)aluminum, trimethylammonium tetra(p-trifluoromethylphenyl)aluminum, tributylammonium tetrapentafluorophenylaluminum, N,N-diethylanilinium tetraphenylaluminum, N,N-diethylanilinium tetrapentafluorophenylaluminum, diethylammonium tetrapentatetraphenylaluminum, triphenylphosphonium tetraphenylaluminum, trimethylphosphonium tetraphenylaluminum, tripropylammonium tetra(p-tolyl)boron, triethylammonium tetra(o,p-dimethylphenyl)boron, tributylammonium tetra(p-trifluoromethylphenyl)boron, triphenylcarbonium tetra(p-trifluoromethylphenyl)boron, triphenylcarbonium tetrapentafluorophenylboron, etc.

[0074] In an embodiment of the present invention, the catalyst may further comprise a support supporting the transition metal compound, the cocatalyst compound, or both. Specifically, the support may support both the transition metal compound and the cocatalyst compound.

[0075] In this case, the support may include a substance containing a hydroxyl group on the surface, and preferably a substance having a highly reactive hydroxyl group and a siloxane group, which has been dried to remove moisture from the surface, may be used. For example, the support may include at least one selected from the group consisting of silica, alumina, and magnesia. Specifically, silica, silica-alumina, and silica-magnesia, etc., dried at high temperatures may be used as the support, and these may usually contain oxide, carbonate, sulfate, and nitrate components such as Na2O, K2CO3, BaSO4, and Mg(NO3)2. These may also include carbon, zeolite, magnesium chloride, etc. However, the support is not limited to these, and is not particularly limited as long as it can support a transition metal compound and a promoter compound.

[0076] The carrier may have an average particle size of 10 to 250 μm, preferably an average particle size of 10 to 150 μm, and more preferably an average particle size of 20 to 100 μm.

[0077] The volume of the micropores in the support may be 0.1 to 10 cc / g, preferably 0.5 to 5 cc / g, and more preferably 1.0 to 3.0 cc / g.

[0078] The specific surface area of ​​the support is 1 to 1,000 m 2 / g, preferably 100 to 800m 2 / g, more preferably 200 to 600m 2 / g.

[0079] In a preferred embodiment of the present invention, the support may be silica. In this case, the drying temperature of the silica may be 200 to 900° C. The drying temperature may be preferably 300 to 800° C., more preferably 400 to 700° C. If the drying temperature is less than 200° C., the moisture content is too high, and the moisture on the surface reacts with the promoter compound, and if the drying temperature exceeds 900° C., the structure of the support may collapse.

[0080] The concentration of hydroxyl groups in the dried silica may be 0.1 to 5 mmole / g, preferably 0.7 to 4 mmole / g, and more preferably 1.0 to 2 mmole / g. If the concentration of hydroxyl groups is less than 0.1 mmole / g, the amount of the first promoter compound supported will be low, and if it exceeds 5 mmole / g, a problem of inactivation of the catalyst component may occur.

[0081] The total amount of the transition metal compound supported on the carrier may be 0.001 to 1 mmole based on 1 g of the carrier. When the ratio of the transition metal compound to the carrier satisfies the above range, appropriate supported catalytic activity is exhibited, which is advantageous in terms of maintaining the activity of the catalyst and in terms of economic efficiency.

[0082] The total amount of the promoter compounds supported on the carrier may be 2 to 15 mmole per gram of carrier. If the ratio of the promoter compounds to the carrier satisfies the above range, it is advantageous in terms of maintaining the activity of the catalyst and economic efficiency.

[0083] One or more types of carriers may be used. For example, both the transition metal compound and the co-catalyst compound may be supported on one carrier, or the transition metal compound and the co-catalyst compound may be supported on two or more carriers. In addition, only one of the transition metal compound and the co-catalyst compound may be supported on the carrier.

[0084] As a method for supporting a transition metal compound and / or a cocatalyst compound that can be used in an olefin polymerization catalyst, a physical adsorption method or a chemical adsorption method may be used.

[0085] For example, the physical adsorption method may be a method in which a solution in which a transition metal compound is dissolved is brought into contact with a support and then dried; a method in which a solution in which a transition metal compound and a promoter compound are dissolved is brought into contact with a support and then dried; or a method in which a solution in which a transition metal compound is dissolved is brought into contact with a support and then dried to produce a support on which a transition metal compound is supported, and separately, a solution in which a promoter compound is dissolved is brought into contact with a support and then dried to produce a support on which a promoter compound is supported, and then these are mixed.

[0086] The chemical adsorption method may be a method in which a promoter compound is first supported on the surface of a carrier, and then a transition metal compound is supported on the promoter compound, or a method in which a catalyst compound is covalently bonded to a functional group on the carrier surface (for example, in the case of silica, a hydroxy group (-OH) on the silica surface).

[0087] In an embodiment of the present invention, the olefin-based polymer may be a homopolymer of an olefin-based monomer or a copolymer of an olefin-based monomer and a comonomer. Preferably, the olefin-based polymer is a copolymer of an olefin-based monomer and an olefin-based comonomer.

[0088] Here, the olefin monomer is C 2-20 α-olefin, C 1-20 Diolefin, C 3-20 Cycloolefin, and C 3-20 At least one selected from the group consisting of cyclodiolefins.

[0089] For example, the olefin monomer may be ethylene, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, or 1-hexadecene, and the olefin polymer may be a homopolymer containing only one of the olefin monomers exemplified above, or a copolymer containing two or more of them.

[0090] In an exemplary embodiment, the olefin polymer comprises ethylene and C 3-20 The olefin-based polymer may be a copolymer in which an α-olefin is copolymerized. Preferably, the olefin-based polymer may be a linear low-density polyethylene in which the olefin-based monomer is ethylene and the olefin-based comonomer is 1-hexene.

[0091] In this case, the ethylene content is preferably 55 to 99.9% by weight, more preferably 90 to 99.9% by weight, and the α-olefin comonomer content is preferably 0.1 to 45% by weight, more preferably 0.1 to 10% by weight.

[0092] Method for producing olefin polymer According to one embodiment of the present invention, there is provided a method for producing an olefin polymer, comprising the step of polymerizing an olefin monomer in the presence of a hybrid catalyst comprising at least one first transition metal compound represented by the following chemical formula 1 and at least one second transition metal compound selected from a compound represented by the following chemical formula 2 and a compound represented by the following chemical formula 3, to obtain an olefin polymer:

[0093] [ka]

[0094] [ka]

[0095] [ka]

[0096] In the above chemical formula, M1, M2, X, and R1 to R 10 is the same as that explained in the section on olefin-based polymers.

[0097] As described above, the olefin polymer produced by the production method according to one embodiment of the present invention has the following characteristics: (1) density of 0.9 to 0.95 g / cm 3 (2) Melt index (I 2.16 (3) the melt index (I 21.6 ) and the melt index (I 2.16 (4) a melt flow ratio (MFR) of 20 or more, (5) a shear thinning index defined by the following mathematical formula 1 of 8 to 15, and (6) an extrusion torque of 270 Nm or less at an extrusion rate of 5.8 to 5.9 kg / hr. A film produced therefrom has a drop impact strength (B type) of 700 g or more based on a thickness of 50 μm.

[0098] [Formula 1] Shear thinning index = η0 / η 500

[0099] Where η and η 500 are the complex viscosities at frequencies of 0.1 rad / s and 500 rad / s, respectively.

[0100] In a specific example of the present invention, the olefin polymer has: (1) a density of 0.915 to 0.945 g / cm 3 (2) Melt index (I 2.16 (3) the melt index (I 21.6) and the melt index (I 2.16 (4) a melt flow ratio (MFR) of 20 or more, (5) a shear thinning index defined by Equation 1 of 9 to 15, and (6) an extrusion torque of 260 Nm or less at an extrusion rate of 5.8 to 5.9 kg / hr. A film produced therefrom may have a drop impact strength (B type) of 700 g or more based on a thickness of 50 μm.

[0101] In a preferred embodiment of the present invention, the olefin polymer has: (1) a density of the olefin polymer of 0.915 to 0.942 g / cm 3 (2) the melt index measured at 190°C under a load of 2.16 kg is 0.5 to 3.5 g / 10 min; (3) the MFR is 20 to 50; (4) the shear thinning index defined by Equation 1 is 9 to 12; and (5) the extrusion load at an extrusion rate of 5.8 to 5.9 kg / hr may be 200 to 255 Nm.

[0102] In embodiments of the present invention, the olefin-based polymer may be polymerized by polymerization reactions such as, but not limited to, free radical, cationic, coordination, condensation, and addition.

[0103] As an embodiment of the present invention, the olefin polymer may be produced by a gas phase polymerization method, a solution polymerization method, a slurry polymerization method, etc. Preferably, the polymerization of the olefin monomer may be carried out by gas phase polymerization, specifically, the polymerization of the olefin monomer may be carried out in a gas phase fluidized bed reactor.

[0104] When olefin polymers are produced by solution polymerization or slurry polymerization, examples of solvents that can be used include C tetrahydrofurans such as pentane, hexane, heptane, nonane, decane, and their isomers. 5-12Examples of the solvent include, but are not limited to, aliphatic hydrocarbon solvents; aromatic hydrocarbon solvents such as toluene and benzene; chlorine-substituted hydrocarbon solvents such as dichloromethane and chlorobenzene; and mixtures thereof.

[0105] Working Example The present invention will be described in more detail below with reference to examples. However, the following examples are merely for the purpose of illustrating the present invention, and the scope of the present invention is not limited to these examples.

[0106] Manufacturing Example The transition metal compound of formula 1-1 (bis(n-propylcyclopentadienyl)hafnium dichloride) and the transition metal compound of formula 2-1 (bis(n-butylcyclopentadienyl)zirconium dichloride) were purchased from TCI and used without further purification.

[0107] 4.47g of the transition metal compound of formula 1-1 and 1.67g of the transition metal compound of formula 2-1 were added to 892g of a 10% methylaluminoxane toluene solution and stirred at room temperature for 1 hour. After the reaction, the solution was added to 200g of silica (XPO-2402), and 1.5 liters of toluene were added and stirred at 70°C for 2 hours. The catalyst after the support was washed with 500ml of toluene and dried overnight in a vacuum at 60°C to obtain 280g of a powdered supported catalyst.

[0108] Examples 1-2 An ethylene / 1-hexene copolymer was produced in the presence of the supported catalyst obtained in Production Example 1 using a gas-phase fluidized bed reactor. The ethylene partial pressure in the reactor was about 15 kg / cm. 2 The polymerization temperature was maintained at 70 to 90°C. The polymerization conditions for the above examples are shown in Table 1 below.

[0109] [Table 1]

[0110] Comparative Example 1 For comparison, Hanwha Chemical's linear low-density polyethylene M1810HA (density 0.9200 g / cm 3 , melt index 1.0 g / 10 min) was used.

[0111] Test Example The physical properties of the olefin polymers of the above examples were measured according to the following methods and standards, and the results are shown in Table 2 below.

[0112] (1) Density Measured according to ASTM D1505.

[0113] (2) Melt index and melt flow ratio (MFR) According to ASTM D1238, the melt index was measured at 190°C under a load of 21.6 kg and 2.16 kg, and the ratio (MI 21.6 / MI 2.16 ) was sought.

[0114] (3) Rheological properties The complex viscosity as a function of frequency was measured using an Anton Parr MCR702 at 190°C, in the frequency range of 0.1 to 500 rad / s, and under 5% strain.

[0115] (4) Push-out load The extrusion load due to the extrusion rate was measured using a Collin Gottfert at 190°C, screw rpm of 20 to 80, and extrusion rates of 1.4 to 5.8 kg / hr. In addition, each resin of the examples and comparative examples was made into a film having a thickness of 50 μm through a 40 mm inflation film extruder (40 mmφ screw, 75 mmφ die, 2 mm die gap). The extrusion conditions were fixed as follows: C1 / C2 / C3 / A / D1 / D2=160 / 165 / 170 / 175 / 180 / 180°C, screw speed 80 rpm, blow-up ratio (BUR) 2.0. The physical properties of the produced films were measured according to the following methods and criteria. The measurement results are shown in Table 2 below.

[0116] (5) Drop impact strength Measurements were performed on a 50 μm thick film in accordance with ASTM D1709 Type B.

[0117] [Table 2]

[0118] The olefin polymer according to the embodiment of the present invention has excellent processability, and an olefin polymer film produced therefrom, specifically a linear low density polyethylene film, has excellent mechanical strength, particularly drop impact strength. [Industrial Applicability]

[0119] Therefore, the present invention can provide an olefin polymer having excellent processability, and a film produced from the same having excellent mechanical strength, particularly excellent drop impact strength.

Claims

1. A method for producing an olefin polymer comprising the steps of: polymerizing an olefin monomer in the presence of a hybrid catalyst comprising at least one first transition metal compound represented by the following chemical formulae 1-1 and 1-2, and at least one second transition metal compound including at least one of the following chemical formulae 2-1, 2-2, and 3-1; The olefin polymer has (1) a density of 0.9 to 0.95 g / cm 3 (2) the melt index (I 2.16 (3) a melt index (I) measured at 190° C. under a load of 21.6 kg; 21.6 ) and the melt index (I 2.16 (4) a melt flow ratio (MFR) of 20 or more, (5) a shear thinning index (defined by the following mathematical formula 1) of 8 to 15, and (6) an extrusion load (torque) of 270 Nm or less at an extrusion rate of 5.8 to 5.9 kg / hr, and a film produced therefrom has a drop impact strength (B type) of 700 g or more based on a thickness of 50 μm. [Formula 1] Shear thinning index = η 0 / 500 In the formula, η 0 and η 500 are the complex viscosities at frequencies of 0.1 rad / s and 500 rad / s, respectively. 【Chemistry 1】 In the above formula, Me is a methyl group.

2. (1) Density is 0.915 to 0.945 g / cm 3 (2) the melt index (I 2.16 (3) a melt index (I) measured at 190° C. under a load of 21.6 kg; 21.6 ) and the melt index (I 2.16 (4) a melt flow ratio (MFR) of 20 or more; (5) a shear thinning index defined by Equation 1 of 9 to 15; and (6) a torque of 260 Nm or less at an extrusion rate of 5.8 to 5.9 kg / hr.

3. The process for producing an olefin polymer according to claim 1, wherein the molar ratio of the secondary transition metal compound to the primary transition metal compound is in the range of 100:1 to 1:

100.

4. The method for producing an olefin polymer according to claim 1, wherein the catalyst comprises at least one promoter compound selected from the group consisting of compounds represented by the following chemical formula 4, compounds represented by the following chemical formula 5, and compounds represented by the following chemical formula 6: 【Chemistry 3】 [Chemical formula 6] [L-H] + [Z(A) 4 ] - Or [L] + [Z(A) 4 ] - In the above formula 4, n is an integer of 2 or more, R a is a halogen atom, C 1-20 Hydrocarbon group or halogen-substituted C 1-20 is a hydrocarbon group, In the above formula 5, D is aluminum (Al) or boron (B), R b , R c , and R d are each independently a halogen atom, C 1-20 Hydrocarbon groups, halogen-substituted C 1-20 Hydrocarbon group, or C 1-20 is an alkoxy group, In the above formula 6, L is a neutral or cationic Lewis base, [L-H] + and [L] + is a Bronsted acid, Z is a Group 13 element, and each A is independently a substituted or unsubstituted C 6-20 an aryl group or a substituted or unsubstituted C 1-20 It is an alkyl group.

5. The method for producing an olefin polymer according to claim 4, wherein the catalyst further comprises a support supporting a transition metal compound, a co-catalyst compound, or both.

6. The method for producing an olefin polymer according to claim 5, wherein the support comprises at least one selected from the group consisting of silica, alumina, and magnesia.

7. The method for producing an olefin polymer according to claim 5, wherein the total amount of the hybrid transition metal compounds supported on the support is 0.001 to 1 mmole based on 1 g of the support, and the total amount of the co-catalyst compounds supported on the support is 2 to 15 mmole based on 1 g of the support.

8. The method for producing an olefin polymer according to claim 1, which is a copolymer of an olefin monomer and an olefin comonomer.

9. The method for producing an olefin polymer according to claim 8, wherein the olefin monomer is ethylene, and the olefin comonomer is at least one selected from the group consisting of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, and 1-hexadecene.

10. The method for producing an olefin polymer according to claim 9, which is a linear low-density polyethylene in which the olefin monomer is ethylene and the olefin comonomer is 1-hexene.

11. The method for producing an olefin polymer according to claim 1, wherein the polymerization of the olefin monomer is carried out by gas phase polymerization.

Citation Information

Patent Citations

  • Method for polymerizing olefin

    JP2003082018A

  • metallocene film resin

    JP2004527594A

  • Dual Metallocene Catalysts for Making Film Resins with Excellent Machine Direction (md) Elmendorf Tear Strength

    JP2007518871A

  • Olefinic polymer

    WO2020080744A1